Engineering students’ perceptions and acceptance of the online flipped classroom for learning during the COVID-19 pandemic - Mohamed Azmin, Nor Fadhillah; Abd Wahab, Mohd Firdaus; Ahmad, Farah; Asnawi, Ani Liza; Jusoh, Ahmad Zamani; Ibrahim, Siti Noorjannah; Jimat, Dzun Noraini (IIUM Press, 2021)
This article reports on the results of an open-response survey sent out to IIUM Engineering students to elicit their thoughts and views about learning their courses online via the flipped learning mode. The decision to take academic courses online was brought about by the COVID-19 pandemic which has forced many sectors, including the education sector, to either cease operations or make changes to their approaches. Hence the objective of the survey was to explore Biochemical Engineering students’ perceptions and acceptance of online flipped learning during the COVID-19 pandemic. Responses were collected from 80 Year 2, 3 and 4 students of Engineering at the IIUM. The results showed an overwhelming acceptance of online flipped learning among the students where only a small percentage of 2.7% completely rejected it as a preferred online learning mode. A majority of the students expressed a reserved acceptance (64.9%) of it, while 27% accepted it unconditionally. A major concern that emerged from the findings was uncurated and poor selection of videos for students to study before class meetings. This suggests that the flipped classroom approach can result in ineffective online learning if it is not designed carefully. The findings have significant implications on the technological skills and pedagogical readiness of university lecturers to design and deliver online flipped learning in an effective manner.